A TLR4 ligand-based adjuvant for promoting the immunogenicity of typhoid subunit vaccines - Alugupalli, Kishore R. (Frontiers in Immunology, 2024)
None of the typhoid Vi Polysaccharide (ViPS) subunit vaccines incorporate adjuvants, and the immunogenicity of ViPS vaccines (e.g. Typbar TCV ® and Typhim Vi ® ) is in part due to associated TLR4 ligands such as endotoxin present in these vaccines. Since endotoxin content in vaccines is variable and kept very low due to inherent toxicity, I hypothesized that incorporating a defined amount of a non-toxic TLR4-ligand such as monophosphoryl lipid A in ViPS vaccines would improve their immunogenicity. To test this hypothesis, I developed an monophosphoryl lipid A-based adjuvant formulation named Turbo. Admixing Turbo with Typbar TCV ® (ViPSconjugated to tetanus toxoid) increased the levels of anti-ViPS IgM, IgG1, IgG2b, IgG2a/c and IgG3 in inbred and outbred mice. In infant mice, a single immunization with Turbo adjuvanted Typbar TCV ® , resulted in a significantly increased and durable IgG response, and improved the control of bacterial burden compared to mice immunized without Turbo. Similarly, when adjuvanted with Turbo, the antibody response and control of bacteremia were also improved in mice immunized with Typhim Vi ® , an unconjugated vaccine. The immunogenicity of unconjugated ViPS is inefficient in young mice and is lost in adult mice when immunostimulatory ligands in ViPS are removed. Nevertheless, when adjuvanted with Turbo, poorly immunogenic ViPS induced a robust IgG response in young and adult mice, and this was observed even under antigen-limiting conditions. These data suggest that incorporation of Turbo as an adjuvant will make typhoid vaccines more immunogenic regardless of their intrinsic immunogenicity or conjugation status and maximize the efficacy across all ages.